EP.TU.266Anatomy teaching to prepare medical students for placements during COVID-19 pandemic: a cross-sectional study on the use of online near-peer teaching. (28th October 2021) - Thirupathirajan, Vikram Ajit Rajan; Georgi, Maria
Abstract: Aims: Medical students have reduced small-group teaching due to the COVID-19 Pandemic. Anatomy is taught thoroughly in pre-clinical years but not specifically during clinical years. We introduced online small-group near-peer anatomy teaching for students in their first clinical year to help them before starting clinical placements. We investigated the usefulness of revisiting anatomy and the effectiveness of small-group teaching in an online setting. Methods: Tutors were 5th or 6th Year medical students, each teaching a group of 5 to 8 tutees anatomy relevant to their clinical placements via Microsoft Teams. Tutees completed a post-tutorial feedback form. The primary outcome was confidence on subject content before and after the tutorial. Each outcome was measured by a Likert Scale, 1 (worst outcome) to 4 (best outcome). Results: 127 feedback responses were analysed, a response rate of 62.0%. Mean tutee confidence improved markedly, from 1.520(SD 0.6281) to 3.079(SD 0.5856, p < 0.0001). The mean score for effectiveness of delivery and the effect of technical issues was 3.811 (SD 0.4127) and 3.667 (SD 0.7114) respectively. Analysis of free-text comments showed that the tutorials had a "really great group size" and were "interactive and well-informed". Conclusions: Clinically relevant anatomy teaching in a small-group-setting is useful in improving students' confidence about the content covered in the placements. The use of online platforms to deliver this in small groups was successful, underwent smoothly and is something that can potentially be implemented in the curriculum.